2013
DOI: 10.1080/1034912x.2013.757141
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Eyewitnesses with Intellectual Disabilities on Photographic Identification Line-ups

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In the current experiment, it is possible that adults with ID were more confident about their responses to the misleading questions for all question types because they had difficultly monitoring the accuracy of their memories. This explanation is consistent with recent research showing that adults with ID had higher confidence—but lower accuracy—than adults without ID in identifying a suspect in a line‐up (Wilcock & Henry, ). Indeed, the authors suggested that adults with ID ‘lack the metacognitive abilities to assess their own recall accuracy’ (p. 50).…”
Section: Discussionsupporting
confidence: 91%
“…In the current experiment, it is possible that adults with ID were more confident about their responses to the misleading questions for all question types because they had difficultly monitoring the accuracy of their memories. This explanation is consistent with recent research showing that adults with ID had higher confidence—but lower accuracy—than adults without ID in identifying a suspect in a line‐up (Wilcock & Henry, ). Indeed, the authors suggested that adults with ID ‘lack the metacognitive abilities to assess their own recall accuracy’ (p. 50).…”
Section: Discussionsupporting
confidence: 91%
“…The study found that despite both groups making the same amount of correct identification, participants with intellectual disabilities were more likely to make a false identification and were also more prone to guessing. Similarly, Wilcock and Henry (2013) found that witness with intellectual disabilities performed poorer in both a target-present and target-absent photographic line-up and were more likely to make a false identification in both conditions. Interestingly, Wilcock and Henry (2013) also found that witnesses with intellectual disability were more confident in their decisions although there was no positive correlation between accuracy and confidence, suggesting that those with intellectual disability lacked insight into their cognitive deficits related to recall accuracy.…”
Section: Brain Injury and Line-up Identificationmentioning
confidence: 83%
“…A limited number of studies have been conducted, however, into the utility or effectiveness of line-up identification methods with witnesses who have cognitive impairments resulting from circumstances such as intellectual disability (e.g. Wilcock & Henry, 2013) and developmental disorders (e.g. Norheim & Ferraro, 2016).…”
Section: Brain Injury and Line-up Identificationmentioning
confidence: 99%
“…Although many crime victims are acquainted with their perpetrator, some are not, and police will likely ask the potential witness to attempt to identify a suspect. Wilcock and Henry (2013) found that adults with ID had poorer performance in identifying perpetrators during a line-up compared with adults without ID. Yet, although performance was poorer, Gawrylowicz et al (2013) found that the difference was not significant and indicated that individuals with ID may be of assistance to the police during eyewitness tasks that rely on face recognition, such as identification in a line-up or looking though a mug-shot book.…”
Section: Identification Of Alleged Perpetratorsmentioning
confidence: 89%